2006
DOI: 10.1021/jp060986k
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study on the Structure and Capillary Phase Transition of a Polymer Melt in a Slitlike Pore:  Effect of Attraction

Abstract: A density functional theory is proposed to investigate the effects of polymer monomer-monomer and monomer-wall attractions on the density profile, chain configuration, and equilibrium capillary phase transition of a freely jointed multi-Yukawa fluid confined in a slitlike pore. The excess Helmholtz energy functional is constructed by using the modified fundamental measure theory, Wertheim's first-order thermodynamic perturbation theory, and Rosenfeld's perturbative method, in which the bulk radial distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…The advantage of this theory is the simplicity of the calculation of the long-range attraction or repulsive interactions. In the previous paper [25], Kim et al have shown that (i) this method is better than the other approximations [18][19][20][21][22][23], which are based on the Taylor density functional expansion with respect to the bulk density, and that (ii) the calculated particle density distributions as well as the thermodynamics are in an excellent agreement with the computer simulation in the wide range of density at the subcritical temperature. In this paper, we extend this method for studying the structure and phase behaviors of an attractive HCY fluid in the nanosized pores.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The advantage of this theory is the simplicity of the calculation of the long-range attraction or repulsive interactions. In the previous paper [25], Kim et al have shown that (i) this method is better than the other approximations [18][19][20][21][22][23], which are based on the Taylor density functional expansion with respect to the bulk density, and that (ii) the calculated particle density distributions as well as the thermodynamics are in an excellent agreement with the computer simulation in the wide range of density at the subcritical temperature. In this paper, we extend this method for studying the structure and phase behaviors of an attractive HCY fluid in the nanosized pores.…”
Section: Introductionmentioning
confidence: 97%
“…The reasons are that (i) many studies had been carried out to investigate the structure and phase behaviors of a bulk HCY fluid [6][7][8][9][10][11][12][13][14][15][16] due to its ability to represent many real fluid system from simple to complex fluids such as charge-stabilized colloidal suspension, micells, protein, and microemulsions, (ii) a few work are done on the structure of an attractive HCY fluid at interfaces [17][18][19][20][21][22][23][24][25], and that (iii) as far as the authors know, the phase behaviors of an attractive HCY fluid at the subcritical temperature, which is confined in the nanopores such as the slit and spherical pores, have not been reported until now. The attractive HCY potential is given by the following expression…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the density functional theory 15,16 for hard-sphere fluids, especially fundamental measure theory (FMT) 17 and its modified version, 18 has been widely employed in the study of Lennard-Jones fluids, 19 Yukawa fluids, 20 chain fluids 21 and electrolyte solutions. 22,23 Rich information about the structural and thermodynamic properties of these systems has been well predicted by using the hard-sphere reference system.…”
Section: Introductionmentioning
confidence: 99%
“…4 A variety of DFT models have been developed to predict the properties of inhomogeneous simple atomic and complex fluids, and those based on Wertheim's first order thermodynamic perturbation theory (TPT1) are promising. [4][5][6][7] For example, Yu et al 8 developed a DFT based on Wertheim's TPT1 for chain conformation and bond orientation correlation function of hard-core multi-Yukawa chain fluids. Borouko et al 9 proposed a DFT to study the phase behavior of a two-component fluid in a slit-like pore with walls modified by tethered chains.…”
Section: Introductionmentioning
confidence: 99%